1999
DOI: 10.1034/j.1399-3054.1999.105310.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of the Arabidopsis AKT1 K+ channel ionic selectivity investigated by expression in yeast of randomly mutated channels

Abstract: The Arabidopsis thaliana K + channel AKT1 was expressed in decreased K + content, and lower growth rate, as compared to control cells expressing the wild-type channel) were selected. a yeast strain defective for K + uptake at low K + concentrations ( B 3 mM). Besides restoring K + transport in this By co-expressing them with the wild-type AKT1 cDNA, it was strain, AKT1 expression increased its tolerance to salt (NaCl shown that the mutated polypeptides were expressed, stable and correctly targeted to the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 57 publications
(88 reference statements)
2
11
0
Order By: Relevance
“…5), probably because SsAKT1 conferred a higher K + uptake capacity in the yeast cells. A similar result was reported by Ros et al (1999), who showed that expressing AtAKT1 in a yeast strain 10A (trk1 − , ura3 − ) defective in high-affinity K + uptake system enhanced salt tolerance. Thus, we speculate that the up-regulation of SsAKT1 expression under saline conditions contributed to mediating significant K + uptake in roots from the external medium, providing S. salsa with the ability to maintain K + homeostasis in the plant under salinity, and ultimately contribute to its salt tolerance.…”
Section: Ssakt1 Might Be Involved In the Salt Tolerance Of S Salsasupporting
confidence: 79%
See 1 more Smart Citation
“…5), probably because SsAKT1 conferred a higher K + uptake capacity in the yeast cells. A similar result was reported by Ros et al (1999), who showed that expressing AtAKT1 in a yeast strain 10A (trk1 − , ura3 − ) defective in high-affinity K + uptake system enhanced salt tolerance. Thus, we speculate that the up-regulation of SsAKT1 expression under saline conditions contributed to mediating significant K + uptake in roots from the external medium, providing S. salsa with the ability to maintain K + homeostasis in the plant under salinity, and ultimately contribute to its salt tolerance.…”
Section: Ssakt1 Might Be Involved In the Salt Tolerance Of S Salsasupporting
confidence: 79%
“…2), which are mainly expressed in roots and involved in K + uptake (Pilot et al 2003). Moreover, the yeast complementation experiments further showed that similar to AtAKT1 in Arabidopsis (Ros et al 1999;Sentenac et al 1992), SsAKT1 could mediate K + uptake over a wide range of external K + concentrations (Figs. 3 and 4); and more interestingly, expression of SsAKT1 could also enhance salt tolerance of a Na + -extruding ATPase-deficient yeast strain G19 via endowing the yeast cells with K + uptake capacity (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The broadest approaches in this context were launched for the Arabidopsis K + channels KAT1 and AKT1. For both, libraries of channels with randomly mutated selectivity filters were generated and screened in the yeast Saccharomyces cerevisiae [60–62]. Lately, a KAT1 mutant library was re‐inspected and over 200 point mutants in the pore region were examined in S. cerevisiae and Xenopus oocytes to assess the effect of the mutations on ion selectivity.…”
Section: Beyond Just Being Doorman – Surprising Facets Of the K+ Selementioning
confidence: 99%
“…In addition to the entrance through specific transporters, Na + may be taken up ectopically through transporters for K + or other ions when Na + is present at a high concentration. Assuming that typical ion concentrations prevailing in a saline soil, in which productivity is decreased, may be around 1 m m K + , 50 m m Na + , and 2 m m Ca 2+ , the putative transporter cannot be any of the well‐established root K + transporters HAK1 or AKT1 because they are not sufficiently permeable to Na + (Ros et al ., 1999; Santa‐María et al ., 1997). The transporter might be LCT1 (Amtmann et al ., 2001), or any of a collection of channels of variable K + /Na + discrimination (Amtmann and Sanders, 1999; Davenport and Tester, 2000; Demidchik et al ., 2002; Leng et al ., 2002; Maathuis and Sanders, 2001; Tyerman and Skerrett, 1999).…”
Section: Introductionmentioning
confidence: 99%